Kapitalisasi Pasar, Profitabilitas, Agresivitas Pajak dan Pengungkapan Corporate Social Responsibility - Putri, Ni Luh Ketut Windy Gangga Maha; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 32 No 9 (2022)DO - 10.24843/EJA.2022.v32.i09.p13, 2022)
The environment in which the company operates must feel the positive impact of the company's existence. The purpose of this research is to examine the effect of market capitalization, profitability, and tax aggressiveness on CSR disclosure. Determination of the sample using purposive sampling technique with several conditions and obtained a number of 139 companies. The observational data obtained were 417 data from 2017 to 2019. The data analysis method used was multiple linear regression analysis. The results of the study found that there was no effect of tax aggressiveness on CSR disclosure. Market capitalization and profitability have a positive influence on CSR disclosure. Keywords: CSR Diclosure; Market Capitalization; Profitability; Tax Aggressiveness